Acceptability, adherence and economic analyses of a new clinical pathway for the identification of non-responders to glaucoma eye drops: a prospective observational study. Issue 12 (4th March 2020) - Waterman, Heather; Read, Simon; Morgan, James Edwards; Gillespie, David; Nollett, Claire; Allen, Davina; Weiss, Marjorie; Anderson, Pippa
Abstract : Background/aims: Assess whether a new clinical pathway for glaucoma was acceptable to patients and healthcare professionals and whether it provided useful clinical information on non-responsiveness and non-adherence to the treatment of elevated intraocular pressure with latanoprost eye drops. Methods: A single arm non-randomised prospective observational study incorporating new glaucoma/ocular hypertension patients. To assess issues of acceptability, qualitative observation and interviews were conducted with patients and healthcare professionals. To determine clinical responsiveness, intraocular pressures were measured before and 4 hours after a clinician-instilled eye drop over two distinct appointments. Adherence data were collected using a Medicine Event Monitoring System. Economic analyses compared the costs between novel and standard care pathways. Results: Of 72 patients approached, 53 entered the study (74.3%) and 50 completed all procedures (94.3%). Intraocular pressure was reduced more than 15% in 83 out of 92 study eyes by final visit (90.2%). The non-response rate was 5.1% once the effect of low adherence was minimised. For the 1376 drop instillation days under observation, eye drops were instilled as prescribed on 1004 days (73.0%), over-instilled on 137 days (9.9%) and not instilled on 235 days (17.1%). The Cardiff Model of Glaucoma Care involved negligible cost, although acceptance for healthcare professionals showed variation. Conclusions: The Cardiff Model of Glaucoma Care offers novel clinical and adherence insights at marginal costs while acceptable to patients. Healthcare professionals felt that 4 hour and 4 week follow-up appointments could cause administrative problems. A streamlined version of the pathway has therefore been developed to facilitate clinical adoption. Trial registration number: ISRCTNID:ISRCTN75888393